1988
DOI: 10.1016/0014-5793(88)80414-9
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide sequence of the androgen‐dependent arginine esterase mRNA of canine prostate

Abstract: The nucleotide sequence of canine prostate arginine esterase mRNA was determined using a 400 bp cDNA clone and primer-extended cDNA transcripts for the 5'coding and noncoding regions. The mRNA contains 864 nucleotides encoding a protein of 236 amino acids preceded by 24 amino acids which constitutes both the signal and the zymogen peptides. The sequence indicates the presence of one potential glycosylation site. A high degree of homology was found between the canine enzyme and other members of the kallikrein f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

1990
1990
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…P09582). 18 PMF analysis of the in-gel digested 28-kd protein band, excised from a nonreducing SDS-PAGE gel, yielded a significant match (P < .05) to the sequence of the same database entry.…”
Section: Identification Of the Ige Antibody-binding Protein As Prostamentioning
confidence: 96%
“…P09582). 18 PMF analysis of the in-gel digested 28-kd protein band, excised from a nonreducing SDS-PAGE gel, yielded a significant match (P < .05) to the sequence of the same database entry.…”
Section: Identification Of the Ige Antibody-binding Protein As Prostamentioning
confidence: 96%
“…Some of these regulatory sequences impart tissue specificity to the expression of adult insect esterases [17]. In mammals, promoter regions necessary for expression of canine prostate arginine esterase have been identified, but the transcriptional regulators binding to these sequences are unknown [18]. Recently, the promoter sequence for JHE has been reported and shown to mediate JH-induced transcription of the JHE gene [6], but specific sequences which mediate JH action have not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…Such identification would greatly contribute to the understanding of KLK family evolution, and more importantly to the development of appropriate animal models for studying the roles of KLKs in both physiological and pathological processes. Although the dog is a species of importance in both veterinary and comparative medicine (Paoloni and Khanna, 2008), only two members of the canine KLK family -dKLK1 and arginine esterase (Chapdelaine et al, 1988;Chapdelaine et al, 1991;Gauthier et al, 1994) -have so far been identified. Recent efforts towards the discovery of novel canine KLKs have been restricted to the detection of putative KLK homologues within whole-genome sequences using computational approaches.…”
Section: Discussionmentioning
confidence: 99%
“…In the dog, only two kallikrein-related peptidases have been detected so far: dKLK1 (Gauthier et al, 1994) and canine arginine esterase, which is now known as dKLK2 (Chapdelaine et al, 1988;Chapdelaine et al, 1991). A recent in-silico analysis of the canine genome identified 14 KLK gene orthologues clustered in tandem on chromosome 1.…”
Section: Introductionmentioning
confidence: 97%